EIF1AX mutation in thyroid tumors: a retrospective analysis of cytology, histopathology and co-mutation profiles - Noha Elsherbini; Dong Hyun Kim; Richard J. Payne; Thomas Hudson; Véronique-Isabelle Forest; Michael P. Hier; Alexandra E. Payne; Marc P. Pusztaszeri (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The EIF1AX mutation has been identified in various benign and malignant thyroid lesions, with a higher prevalence in poorly differentiated thyroid carcinoma (PDTC) and anaplastic thyroid carcinoma, especially when combined with RAS or TP53 mutation. However, data and clinical significance of EIF1AX mutations in thyroid nodules is still limited. We investigated the prevalence of EIF1AX mutations and co-mutations in cytologically indeterminate thyroid nodules at our institution. Methods A 5-year retrospective analysis was performed on surgically resected thyroid nodules with identified EIF1AX mutations on molecular testing with ThyroseqV3®. Mutation type and presence of co-mutations were correlated with histopathologic diagnosis and clinical characteristics. Histopathology diagnoses were subsequently categorized as benign, borderline, malignant or aggressive malignant (≥ 10% PDTC component). Chi-square test was used to compare the malignancy associations of the: 1) A113_splice mutation compared to non-A113_splice mutations 2) singular A113_splice mutations compared to singular non-A113_splice mutations. Fisher’s Exact Test was used to determine the association of A113_splice mutation with aggressive malignancies compared to non-A113_splice mutations. A p value of 0.05 or less was considered statistically significant. Results Out of 1583 patients who underwent FNA, 621 had further molecular testing. 31 cases (5%) harbored EIF1AX mutations. Of these cases, 12 (38.7%) were malignant, 2 (6.5%) were borderline, and 17 (55%) were benign. 4/31 cases (13%) were aggressive malignant (≥ 10% PDTC component). The most prevalent mutation was the A113_splice mutation at the junction of intron 5 and exon 6 (48%). All other mutations, except one, were located at the N-terminal in exon 2. 7/31 cases (22.6%) harbored ≥ 1 co-mutation(s), including 4 RAS, 3 TP53, 1 TERT and 1 PIK3CA, with 86% of them being malignant. All 4 nodules with RAS co-mutations were malignant including one PDTC. Conclusion Our study reports the largest cohort of EIF1AX mutations in Bethesda III/IV FNA samples with surgical follow-up to our knowledge. The presence of the EIF1AX mutation confers a 45.2% risk of malignancy (ROM) or borderline after surgery. However, the coexistence of EIF1AX mutations with other driver mutations such as RAS, TERT or TP53 conferred an 86% ROM. While 55% of thyroid nodules were benign at the time of surgery, the possible malignant transformation of these nodules, had they not been resected, is unknown. Finally, 13% of the nodules with EIF1AX mutations were aggressive with a significant PDTC component. These findings can further aid in clinical decisions for patients with thyroid nodules. Graphic Abstract